What explains trends in labor force participation of older men in the United States? - David M. Blau; Ryan Goodstein (Institute for the Study of Labor (IZA), 2007)
After nearly a full century of decline, the Labor Force Participation Rate (LFPR) of older men in the United States leveled off in the 1980s, and began to increase in the late 1990s. We use a time series of cross sections from 1962 to 2005 to model the LFPR of men aged 55-69, with the aim of explaining these trends. We investigate the effects of changes in Social Security rules, lifetime earnings, pension coverage, wages, health, health insurance, and the educational composition of the labor force. Our results indicate that the decline in the LFPR from the 1960s through the 1980s cannot be explained by any of these factors. The recent increase in the LFPR of older men can be explained by changes in the composition of the older male population away from high school dropouts and toward college attendees and graduates. Changes in Social Security may have contributed to the recent increase as well, but the results for Social Security are sensitive to specification.
Keywords: 330; Ältere Arbeitskräfte; Männliche Arbeitskräfte; Erwerbstätigkeit; Altersgrenze; Gesetzliche Rentenversicherung; USA